Hydroisomerization Of Paraffin Wax Of Sumatran Light Waxy Residue For Lubricating Oil And Fuel Oils Production Using The BI - Functional Catalysts With Various Acid Supports - A.S Nasution (Scientific Contributions Oil and Gas, 1982)
Paraffin wax (average mol wt 750-850) of Sumatran Light Waxy Residue was hydroisomerized by bi-functional catalyst with various acidic com- ponents, using a catetest unit, operated at high temperature and pressure with continous system . The reaction products were distilled at at- mospheric pressure to 380Â°C and the residues subjected to a dewaxing treat ment at - 20Â°C. Based on this separation the reaction products were regarded as pseudo three component systems the component being lubricating oil, unconverted wax and cracked products. The lubricating oils obtained in the experiments have a-viscosity index of 122- 16S, With M/AI0-SIO2 type catalyst a maximal oil yield of 28,0 per cent wt was obtained with 25 per cent of cracked products. And at 50 percent by wt of feedstock conversion, the smoke point of kerosene and diesel index of gas oil are 34 and 87 mm respectively. The wux contents in the feedstock is an important source for high viscosity index lubricating oil produC tion obtained by hydroisomerization of this wax.